Pengaplikasian Tandem Walking Exercise Dalam Memperbaiki Keseimbangan Pada Lansia: (Narrative Review) - Kadek Suci Lestari Putri; Yulis Susanti; Ezra Bernardus Wijaya (CV. KAMPUS AKADEMIK PUBLISING, 2024)
while an activity, tandem walking involves reducing the foot's area of support while you walk in a straight path while contacting your other toes with your heel. The goal of this exercise is to stimulate a dynamic improvement in postural balance. Finding out how Tandem Walking affects geriatric balance is the primary goal of this research. This research method uses a literature review approach. Literature was obtained from 2 data bases, namely: Sematic Scholar and Google Scholar. The research sample is elderly people with balance disorders, giving Tandem Walking Exercises, male and female, publication year is the last 10 years (2014-2024), variables measured are the BBS, TUGT. Based on the 20 pieces of literature collected, the results showed that the most dominant literature in 2020 was 17 pieces of literature, a study design with an average of Quasi Experiments and 3 pieces of literature with case studies. All journals analyzed show that Tandem Walking is significantly effective in improving balance in the elderly